Lawrence of Arabia the battle for the Arab World - Keane, John E. 1952-
A story of courage and guilt, betrayal and triumph of T.E. Lawrence
Orig.: GB 2003
Keywords: Lawrence, T. E. / (Thomas Edward) / 1888-1935; Great Britain / Army / Biography; Geschichte 1900-2000; Soldiers / Great Britain / Biography; World War, 1914-1918 / Campaigns / Middle East; Geschichte; Weltkrieg (1914-1918); Middle East / History / 20th century; Großbritannien; Naher Osten; Biografie